PERFORMANCE AND DIGESTIVE TRACT DEVELOPMENT OF YOUNG BROILER CHICKENS FED MASH BASAL DIET SUPPLEMENTED WITH RICE HULLS OR WHEAT POLLARD AT DIFFERENT LEVELS - Hartini, S.; Kayadoe, M.; Rahardjo, D.D. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
An experiment was conducted to determine the effect of different insoluble non-starchpolysaccharides (NSP) sources supplementation at levels 0, 20, 40, 60 g/kg on performance anddigestive tract development of young broilers (doc-21 d). Results showed that there were no interactionsbetween insoluble NSP sources and levels at any variable measured. Only levels of insoluble NSP hadsignificant effect. Young broilers fed mash basal diet supplemented with 6% insoluble NSP decreasedbody weight gain (P<0.05) and impaired gain-to-feed ratio (P<0.01). Diets did not have a significanteffect on feed intake (FI), in addition to the relative weight of gizzard, jejunum-ileum, caeca, andpancreas. Levels of NSP affected the weight of gastrointestinal digesta with jejunal-ileal digesta wasfound to be the highest (P<0.01) in 6% insoluble NSP supplementation. Dry matter of jejunal-ilealdigesta and excreta moisture also did not significantly affected by diets (P≥0.05). The present studydemonstrated that the insoluble NSP can be supplemented to young broilers diet up to 4%. It is likelythat increased performance of young broilers supplemented with insoluble NSP up to 4% was due toincrease FI and a better gut environment. The supplementation of insoluble NSP did not produce strongimpact considering that the diets were given in mash form.